Pekembangan Moral Dalam Berbagi Nasi: Aspek Etika Sosial dalam pemberian Makanan kepada Masyarakat - Danang Nugroho; Raihanavis Ishaq; Nur Kholis Tamami; Mohamad Arifin; Muhammad Ridwan Dimyati; Muhammad Zahran Irsyad; Muhammad Rizki Maulana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to look at moral developments in rice sharing practices from the social ethical aspects of giving food to the community. The research uses a qualitative approach and involves observations, and analysis of documents related to rice sharing practices. The ethical aspects that emerge in this practice include moral considerations, justice of distribution, and social responsibility. On the basis of stakeholder theory, ethics of the evaluation theory and the theory of justice, this research is expected to make significant contributions to ensuring that rice sharing practices are carried out with strong and responsible moral principles. In addition, the study also provides insights into the motives, social responsibility, and impact of rice sharing practices on society. It is expected to provide a better understanding of the ethical aspects involved in rice sharing practice. Therefore, it will be useful to understand the moral development involved in the practice of sharing rice as well as to develop ethical guidelines that can help social actors and the general public to carry out rice sharing.